Arquitetura de hardware multicanal reconfigurável com excitação multinível para desenvolvimento e testes de novos métodos de geração de imagens por ultrassom - Assef, Amauri Amorin (2013)
Medical ultrasound (US) scanners are amongst the most sophisticated signal processing machines in use today. Even with the recent advances in electronic technology, their typical architecture is often “closed” and does not fit the requirements of flexibility and RF data access to the development and test of new modalities and US techniques. This work presents the development of a novel modular hardware architecture (front-end), FPGA-based (Field Programmable Gated Array) and software (back-end), PC-based or DSP-based, fully programmable, open and flexible, for research and investigation of new techniques for medical US imaging. The proposed platform, ULTRA-ORS (Ultrasound Open Research System), allows connection to linear, convex and phased array transducers with center frequency between 500 kHz and 20 MHz, and expansion capability for operation with transducers up to 1024 multiplexed elements. The transmitter beamformer can excite simultaneously, using PWM signals, 128-channel with arbitrary waveform, programmable aperture, and 200 Vpp excitation voltage, allowing individual enable control, amplitude apodization up to 256 levels, phase angle and proper time delay for focusing on transmission. The receiver beamformer can handle simultaneous 128-channels acquisition with programmable sampling rate up to 50 MHz and 12-bit resolution. As essential item of this work, the platform enables access to the raw RF signals to be transferred to a computer through serial ports or DSP kits for imaging processing. As a result of the research project, we present a new digital US system that can be used for evaluation of images generated by the beamforming technique, using as reference the Field II simulation tool and comparisons with commercial equipment using US tissue-mimicking phantom.